Fusicoccane glycosides from the endophytic fungus Talaromyces sp. DC-26 - Peng Zhou; Jingwen Yu; Xueying Deng; Jinyan Cai; Wenya Feng; Junjun Liu; Qin Li; Chong Dai; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

Molybdate ion adsorption enhances the chlorine corrosion resistance of NiFe-LDH to stabilize the oxidation mechanism of alkaline seawater - Ziyi Jia; Weiwei Bao; Taotao Ai; Jie Han; Zhifeng Deng; Hongfeng Dong; Junjun Zhang (Chemical Engineering Journal, 2026)

Engineered norfloxacin-derived carbonized polymer dots for synergistic antibacterial and anti-inflammatory periodontitis therapy - Xinyu Jiang; Yu Deng; Jia Liu; Huan Chen; Hongyan Lin; Yu Zhong; Junjun Liu; Xinchan Liu; Bai Yang (Chemical Engineering Journal, 2026)

From bigger batteries to new charging realities - Weipeng Zhan; Yuan Liao; Sonia Yeh; Junjun Deng; Zhenpo Wang; Dingsong Cui (Transportation Research Part D: Transport and Environment, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

Integrated chemometrics and untargeted metabolomics reveal the differential effects of drying methods on the quality of Sharen (Amomum villosum Lour.) - Zhixia Sun; Jun Chen; Junjun He; Ivan Shorstkii; Liqing Du; Taotao Dai; Yihui Wang; Yanli Yao; Chengmei Liu; Lizhen Deng (Food Bioscience, 2026)

Molecular mapping of a novel non-canonical gibberellin-sensitive dwarfing gene Rht29 in wheat (Triticum aestivum) - Fuqiao Deng; Juanyu Zhang; Yanyan Tang; Furong Huang; Tao Li; Haili Zhang; Jinhui Wang; Junjun Liang; Guangbing Deng; Hai Long (Theoretical and Applied Genetics, 2026)

Antibiotic pollution impedes nitrogen elimination rates and increases N2O emission from wetlands: A multilevel meta-analysis and the mechanisms - Jibao Jia; Yaxin Chen; Yang Li; Yuting Jiang; Deshou Cun; Yun Zhou; Shengjiong Deng; Junjun Chang (Journal of Environmental Chemical Engineering, 2026)

Use of stable nitrogen isotopes in atmospheric aerosol research - Jingqi Bai; Libin Wu; Qingzi Zhao; Ke Xin; Wei Hu; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2026)

A new and simple hypoplastic model for saturated soils reinforced by plant roots - Shusen Liu; Junjun Ni; Xudong Zhao; Yufeng Gao; Ning He; Yongfeng Deng (Computers and Geotechnics, 2026)

Increasing CO2 and CH4 emissions from constructed wetlands under composite pollution of microplastics and perfluorooctanoic acid: altering the interactions between dissolved organic matter and the functional microbiome - Yun Zhou; Mingwei Li; Shengkun Yang; Deshou Cun; Shengjiong Deng; Erik Jeppesen; Junjun Chang (Chemical Engineering Journal, 2026)

Enhanced osteogenic differentiation of rBMSCs under low-frequency dynamic stimulation of piezoelectric membranes - Jing Liu; Donglin Li; Xiaoqing Liu; Jiahao Zeng; Yuxuan Lu; Weiqiang Fan; Shuncheng Zhang; Yuxuan Jia; Linxuan Zheng; Xin Chen; Hongzhang Deng; Yongmei Wang; et al. (Chemical Engineering Journal, 2026)

Distinct phylogenetic patterns and assembly processes of abundant and rare taxa in traditional grain vinegar fermentation ecosystem - Mingye Peng; Bo Li; Yunli Zhu; Lu Guo; Lei Deng; Zhicong Shen; Zhiwen Jia; Yang Chen; Junjun Gao; Mengzhou Zhou (International Journal of Food Microbiology, 2026)

Genetic and transcriptomic identification of WPG1 controlling nitrogen allocation-related leaf chlorisis and premature senescence in wheat - Haili Zhang; Li’ao Zhang; Qiang Li; Ling Yi; Juanyu Zhang; Yanyan Tang; Jinhui Wang; Junjun Liang; Tao Li; Fangyan Zhang; Yiran Cheng; Yi Wang; et al. (Theoretical and Applied Genetics, 2026)

On field measurement for absorption properties of biomass burning aerosols in the North China Plain and climate implications - Yang Wang; Yansong Xu; Ruonan Bian; Junjun Deng; Yichen Ma; Song Guo; Jing Wang (Science China Earth Sciences, 2026)

Greenhouse gas emissions from field-scale surface-flow constructed wetlands fed with different polluted water types: Environmental and microbial drivers - Deshou Cun; Xiaowan Chen; Junjun Chang; Yang Li; Rong Wu; Rufeng Lin; Shengjiong Deng; Erik Jeppesen; Changqun Duan (Journal of Hydrology, 2025)

Experimental and DEM investigation of root orientation effects on shear behavior of soils subjected to freeze–thaw cycles - Junjun Ni; Haoyu Zhang; Shusen Liu; Yongfeng Deng; Ning He (Engineering Geology, 2025)

Light absorption and molecular composition of brown carbon in Nanjing, China: Large contribution of biomass burning and secondary formation - Junjun Deng; Xinfeng Wang; Jialei Zhu; Wei Hu; Libin Wu; Pingqing Fu (Journal of Environmental Management, 2025)

Characteristics and influencing factors of bacterial, archaeal and fungal community assemblage in riparian restored wetlands: The distinctions between the influent and effluent zones - Shengjiong Deng; Deshou Cun; Yang Li; Lixia Wang; Lingwei Kong; Junjun Chang (Process Safety and Environmental Protection, 2025)

Machine learning-based sweet spot prediction for lacuscrine shale oil in the Weixinan Sag, Beibu Gulf Basin, China - Ruoxin Huang; Yifan Li; Zhiqian Gao; Caiwei Fan; Junjun You; Ruisi Li; Chengkun Deng; Guocui Li (Marine and Petroleum Geology, 2025)

High chemodiversity of nitrogen-containing organic compounds in vehicle emissions driven by transformative reactions - Shuang Chen; Yisheng Xu; Dandan Liu; Junjun Deng; Rui Liu; Shaofei Kong; Pingqing Fu (Journal of Hazardous Materials, 2025)

Unveiling how reconstructed molybdenum oxyanions enhances the alkaline oxygen evolution reaction - Yize Wang; Jie Han; Weiwei Bao; Taotao Ai; Junjun Zhang; Zhifeng Deng; Peng Jiang (Chemical Engineering Journal, 2025)

Harnessing FDA-approved dipyridamole to inhibit NLRP3 inflammasome and improve outcomes of acute lung injury in sepsis - Xiuhui Chen; Yutong Zheng; Xiaofeng Zhang; Anran Zheng; Junjun Huang; Guoliang Deng; Xuna Wu; Yuying Peng; Xiaoling Zhang; Renshan Chen; Qing Xiao; Weijun Ye (Toxicology and Applied Pharmacology, 2025)

Influence of soil crack on large-deformation consolidation of dredged clay under vacuum preloading: A numerical solution - Guizhong Xu; Yifei Liu; Junjun Ni; Yupeng Cao; Sifang Deng (Computers and Geotechnics, 2025)

Genetic identification and characterization of quantitative trait loci for wheat grain size-related traits independent of grain number per spike - Tao Li; Yanyan Tang; ZhengXi Lin; Jinghui Wang; Juanyu Zhang; Qiang Li; Furong Huang; Junjun Liang; Haili Zhang; Zehou Liu; Jun Li; Wuyun Yang; et al. (Theoretical and Applied Genetics, 2025)

A multiple‐behaviors virtual fish model for simulating fish trajectory in vertical slot fishways - Xiaolong Chen; Xiaotao Shi; Xingyong Deng; Majid Rasta; Junjun Tan; Yu Wang; Yongqiang Jiang; Yanqin Bai (Journal of Fish Biology, 2025)
Fishways are essential for restoring river connectivity and facilitating fish migration, necessitating ongoing research for efficiency optimization. This study developed a fish behavior model to optimize fishway efficiency cost‐effectively. The model simulates swimming trajectories of Schizothorax wangchiachii within a vertical slot fishway incorporating upstream behavior, random behavior, obstacle avoidance, and swimming speed variations. The simulated trajectory exhibits a high consistency with 20 real trajectories, achieving a trajectory overlap rate of 86.7%. This result highlights the model's ability to accurately simulate fish movements, demonstrating its significant potential to revolutionize fishway design.

NiVFe-LDH nanosheets reinforced MoS2 heterogeneous interface design for glycol-assisted water electrolysis - Suzhao Yang; Jie Han; Weiwei Bao; Taotao Ai; Xueling Wei; Peng Jiang; Zhifeng Deng; Junjun Zhang (Fuel, 2025)

Seismic performance of precast double-column rocking piers with U-shaped tendons and stiffening steel shoes: Experimental and numerical study - Haiqiang Zhong; Junjun Guo; Xinzhi Dang; Xiaowei Deng; Wancheng Yuan; Zhiqiang Wang (Engineering Structures, 2025)

Lake pollution control and restoration: A critical review of strategies and measures for plateau lakes in Southwestern China - Shengjiong Deng; Lingjuan Tao; Yang Li; Ping Lan; Lixia Wang; Deshou Cun; Junjun Chang (Ecological Engineering, 2025)

Durability and degradation mechanisms of dredged clays stabilized with ternary geopolymer under cyclic drying-wetting environments - Jianhua Wang; Yongfeng Deng; Cong Mou; Jianwen Ding; Junjun Ni; Xing Wan (Bulletin of Engineering Geology and the Environment, 2025)

Self-Assembled Arachidonic Acid Nanomicelles for Radiation-Induced Ferroptosis to Enhance Tumor Radioimmunotherapy - Jiadong Wang; Yueyue Jing; Li Liu; Pengfei Xing; Zheng Deng; Yifan Zhang; Xirui Wu; Bin Hu; Cai Zhang; Xianglong Sun; Yuqian Liu; Jiawei Liu; et al. (Chemical Engineering Journal, 2025)

An efficient fungi-biochar-based system for advancing sustainable management of combined pollution - Ying Xia; Minghui Deng; Tao Zhang; Junjun Yu; Xinda Lin (Environmental Pollution, 2025)

Insights from Computational Fluid Dynamics and In Vitro Studies for Stent Protrusion in Iliac Vein: How Far Shall We Go? - Zhenmin Fan; Jian Lu; Hao Cheng; Xia Ye; Xiaoyan Deng; Pengfei Zhao; Junjun Liu; Mingyuan Liu (Cardiovascular Engineering and Technology, 2025)

Enhanced remediation of real agricultural runoff in surface-flow constructed wetlands by coupling composite substrate-packed bio-balls, submerged plants and functional bacteria: Performance and mechanisms - Shengjiong Deng; Deshou Cun; Rufeng Lin; Dongliang Peng; Yanduo Du; Aoxue Wang; Bowen Guan; Rong Tan; Junjun Chang (Environmental Research, 2024)

Study on the characteristics of urban background ozone pollution based on long-term observations from mountain sites in China during 2015–2022 - Wei Zhao; Bo Gao; Junjun Deng; Jiaren Sun; Laiguo Chen; Shaojia Fan (Atmospheric Research, 2024)

Fine mapping and candidate gene mining of QSc/Sl.cib-7H for spike compactness and length and its pleiotropic effects on yield-related traits in barley (Hordeum vulgare L.) - Jinhui Wang; Yanyan Tang; Jin Li; Juanyu Zhang; Furong Huang; Qiang Li; Baowei Chen; Li’ao Zhang; Tao Li; Haili Zhang; Junjun Liang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2024)

Effective remediation of agricultural drainage at three influent strengths by bioaugmented constructed wetlands filled with mixture of iron‑carbon and organic solid substrates: Performance and mechanisms - Deshou Cun; Haoyu Wang; Ming Jiang; Rufeng Lin; Shengjiong Deng; Junjun Chang; Yonggui Zhao; Changqun Duan (Science of The Total Environment, 2024)

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

The spatiotemporal heterogeneity of microbial community assembly during pit fermentation of soy sauce flavor baijiu - Liang Yang; Xiaodong Huang; Jiafeng Hu; Hong Deng; Junjun He; Chunlin Zhang (Food Bioscience, 2024)

Experimental and numerical investigation on seismic performance of novel cable-restraining composite rubber bearings for highway bridges - Haiqiang Zhong; Junjun Guo; Xinzhi Dang; Xiaowei Deng; Wancheng Yuan; Zhiqiang Wang (Engineering Structures, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

High acidity notably influences acid mine drainage treatment performance in constructed wetlands packed with composite organic substrates by affecting both abiotic and biotic routes - Deshou Cun; Shengjiong Deng; Xuan Li; Fan Yang; Junjun Chang; Pengchang Duan; Changqun Duan (Chemical Engineering Journal, 2024)

Molecular composition and sources of free amino acids in atmospheric aerosols from Mt. Tai and a nearby city - Qingzi Zhao; Libin Wu; Xiaoli Fu; Wei Hu; Yajie Wang; Yuantao Wang; Ke Xin; Jingjing Meng; Siyao Yue; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2024)

Application of microbially induced calcium carbonate precipitation (MICP) process in concrete self-healing and environmental restoration to facilitate carbon neutrality: a critical review - Junjun Chang; Dongyang Yang; Cheng Lu; Zhitao Shu; Shengjiong Deng; Liwei Tan; Shaoqing Wen; Ke Huang; Pengchang Duan (Environmental Science and Pollution Research, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Seismic assessment and parametric analysis on a multi-level aseismic simply-supported bridge with cable-restraining composite rubber bearings and dissipative controlled rocking piers - Haiqiang Zhong; Junjun Guo; Wancheng Yuan; Zhiqiang Wang; Xinzhi Dang; Xiaowei Deng (Soil Dynamics and Earthquake Engineering, 2024)

Seasonal purification efficiency, greenhouse gas emissions and microbial community characteristics of a field-scale surface-flow constructed wetland treating agricultural runoff - Xiaowan Chen; Shengjiong Deng; Bohua Ji; Suqing Wu; Junjun Chang (Journal of Environmental Management, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Land use regulates the spectroscopic properties and sources of dissolved organic matter in the inflowing rivers of a large plateau lake in southwestern China: implication for organic pollution control - Rong Wu; Weijie Guo; Yutong Li; Shengjiong Deng; Junjun Chang (Environmental Science and Pollution Research, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Computational identification and systematic classification of cytochrome P450 genes in Pogostemon cablin provide insights into flavonoids biosynthesis - Junjun Li; Cao Deng; Mengjia Liu; Yang He (Acta Physiologiae Plantarum, 2023)

Diurnal variations in primary and secondary organic aerosols in an eastern China coastal city: The impact of land-sea breezes - Qiang Zhang; Wei Hu; Hong Ren; Jianbo Yang; Junjun Deng; Dawei Wang; Yele Sun; Zifa Wang; Kimitaka Kawamura; Pingqing Fu (Environmental Pollution, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Numerical study on seismic performance of a novel multi-level aseismic highway bridge with cable-sliding friction aseismic bearings and dissipative controlled rocking piers - Haiqiang Zhong; Junjun Guo; Wancheng Yuan; Zhiqiang Wang; Xinzhi Dang; Xiaowei Deng (Engineering Structures, 2023)

Impacts of regional uplift of the Tibetan Plateau on local summer precipitation and downstream moisture budget: A simulation study - Kai Yang; Jinghua Chen; Chunsong Lu; Junjun Li; Tianyu Liu; Liping Deng; Yanwei Li (International Journal of Climatology, 2022)
Using the Weather Research and Forecasting (WRF) model, a series of sensitivity experiments were conducted to study the individual and overall effects of the various topographic uplifts of the Tibetan Plateau (TP) on regional climate variability. The presence of the southern slope of the TP facilitates the maintenance and development of the South Asia High (SAH), which produces a positive cyclic response between local precipitation and SAH, so that the northern branch of the South Asian summer monsoon (SASM) maintains the water vapor supply. At the same time, the southern slope of the TP has a positive effect on the mid‐latitude tropospheric anomalous cyclone and anticyclone systems which promotes the downstream advancement of the East Asian summer monsoon (EASM) and is favourable for the transfer of water vapor and convective clouds downstream. The role of the TP platform is mainly due to the lifting of moisture generated by its local heating, which favours the formation of local convective clouds and precipitation while causing nonadiabatic warming of the troposphere. Water vapor transported from the TP could affect precipitation in central‐eastern China (CEC). However, the supply of water vapor in Southern East China (SEC) mainly comes from the southeast coast of China. The Tibetan Plateau sensitive areas (TPSA) have impacts on the water vapor transport path. Removing the TPSA favours an increase in precipitation and convective clouds in SEC. The removal of topographic disturbances favours the convergence and dispersion of water vapor at mid‐latitudes. The mid‐latitude dynamical anomaly may form a standoff with the low‐latitude dynamical system. This leads to inefficient precipitation and convective generation processes, a weakened monsoon advance over land, and a southward shift in the rainfall belt.

Identification of PP2C Genes in Tibetan Hulless Barley (Hordeum vulgare var. nudum) Under Dehydration Stress and Initiatory Expression and Functional Analysis of HvPP2C59 - Junjun Liang; Ling Yi; Lilan Li; Haili Zhang; Yunshu Zhang; Guangbing Deng; Hai Long; Maoqun Yu (Plant Molecular Biology Reporter, 2022)

Genetic and transcriptomic dissection of an artificially induced paired spikelets mutant of wheat (Triticum aestivum L.) - Juanyu Zhang; Yanyan Tang; Xi Pu; Xuebing Qiu; Jinhui Wang; Tao Li; Zhao Yang; Yao Zhou; Yuxiao Chang; Junjun Liang; Haili Zhang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2022)

Genetic dissection of quantitative trait loci for grain size and weight by high-resolution genetic mapping in bread wheat (Triticum aestivum L.) - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Juanyu Zhang; Xvebing Qiu; Xi Pu; Wuyun Yang; Jun Li; Zehou Liu; et al. (Theoretical and Applied Genetics, 2022)

Identification of HvLRX, a new dehydration and light responsive gene in Tibetan hulless barley (Hordeum vulgare var. nudum) - Junjun Liang; Haili Zhang; Ling Yi; Yawei Tang; Hai Long; Maoqun Yu; Guangbing Deng (Genes & Genomics, 2021)

Identification and validation of two major QTLs for spike compactness and length in bread wheat (Triticum aestivum L.) showing pleiotropic effects on yield-related traits - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Xvebing Qiu; Xi Pu; Jun Li; Zehou Liu; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

LncRNA NEAT1 Enhances Glioma Progression via Regulating the miR-128-3p/ITGA5 Axis - Jiakai Chen; Handong Wang; Junjun Wang; Wenhao Niu; Chulei Deng; Mengliang Zhou (Molecular Neurobiology, 2021)
Accumulating evidences indicate that long non-coding RNA nuclear paraspeckle assembly transcript 1 (NEAT1) promotes the progression of glioma. In this study, we postulated that NEAT1 may act as a miR-128-3p sponge. Relative levels of NEAT1 and miR-128-3p expression in human glioma samples and GBM cells were detected using quantitative real-time PCR. By means of CCK-8 assays, transwell assays, and flow cytometric analysis, the biological functions of miR-128-3p and NEAT1 were investigated in U87MG and U251MG human GBM cell lines with stable miR-128-3p and NEAT1 knockdown or overexpression. The luciferase reports, RNA pull-down assay, and RNA immunoprecipitation assay were conducted to determine the relevance of NEAT1 and miR-128-3p in glioma. As a result, high expression of NEAT1 and lack of miR-128-3p were observed in glioma specimens and cells. By binding to anti-oncogene miR-128-3p in the nucleus, NEAT1 enhanced tumorigenesis and glioma development. Further experiments suggested that ITGA5 expression was increased in glioma tissues and was found to be connected with miR-128-3p. Additionally, NEAT1 facilitated ITGA5 expression via competitively binding to miR-128-3p. For this reason, ITGA5 would not be decomposed by miR-128-3p and could activate FAK signaling pathway, thereby promoting cell growth. Collectively, these results indicated that the NEAT1/miR-128-3p/ITGA5 axis was involved in glioma initiation and progression, and might offer a potential novel strategy for treatment of glioma.

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

An improved method used for evaluating potential environmental pollution risk based on spatial distribution and density of farms - Jianghui Wen; Bianyu Zhen; Zhenyu Pu; Xia Peng; Junjun Tan; Zhongbao Shao; Bosheng Bao; Zhiping Ran; Qishuang Gao; Bing Deng (Environmental Science and Pollution Research, 2021)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Cr(VI) removal performance from aqueous solution by Pseudomonas sp. strain DC-B3 isolated from mine soil: characterization of both Cr(VI) bioreduction and total Cr biosorption processes - Junjun Chang; Shengjiong Deng; Yun Liang; Jinquan Chen (Environmental Science and Pollution Research, 2019)

Composition, mixing state, and size distribution of single submicron particles during pollution episodes in a coastal city in southeast China - Lingling Xu; Xin Wu; Zhenyu Hong; Yanru Zhang; Junjun Deng; Youwei Hong; Jinsheng Chen (Environmental Science and Pollution Research, 2019)

Nitrogen Removal Performance and Enzyme Activities of Baffled Subsurface-Flow Constructed Wetlands with Macrophyte Biomass Addition - Junjun Chang; Shengjiong Deng; Wei Jia; Peng Chen; Yao Wang; Jinquan Chen (Water, Air, & Soil Pollution, 2018)

Spatiotemporal distribution and source apportionment of low molecular weight organic acids in wet precipitation at a coastal city, China - Wenjiao Du; Zhenyu Hong; Yanting Chen; Junjun Deng; Jinsheng Chen; Lingling Xu; Youwei Hong; Hang Xiao (Environmental Science and Pollution Research, 2017)

Secreted expression of truncated capsid protein from porcine circovirus type 2 in Pichia pastoris - Xiaohong Chen; Junjun Chen; Yuanxing Zhang; Ping Zhu; Yong Deng; Qin Liu (Biotechnology Letters, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

A Single Nucleotide Polymorphism of Nud Converts the Caryopsis Type of Barley (Hordeum Vulgare L.) - Shuiyang Yu; Hai Long; Guangbing Deng; Zhifen Pan; Junjun Liang; Xingquan Zeng; Yawei Tang; Nyima Tashi; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Localization of the powdery mildew resistance gene Pm07J126 in wheat (Triticum aestivum L.) - Shuiyang Yu; Hai Long; Guangbing Deng; Zhifen Pan; Junjun Liang; Maoqun Yu (Euphytica, 2015)

Soil organic matter quantity and quality shape microbial community compositions of subtropical broadleaved forests - Junjun Ding; Yuguang Zhang; Mengmeng Wang; Xin Sun; Jing Cong; Ye Deng; Hui Lu; Tong Yuan; Joy D. Van Nostrand; Diqiang Li; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2015)
As two major forest types in the subtropics, broadleaved evergreen and broadleaved deciduous forests have long interested ecologists. However, little is known about their belowground ecosystems despite their ecological importance in driving biogeochemical cycling. Here, we used Illumina MiSeq sequencing targeting 16S rRNA gene and a microarray named GeoChip targeting functional genes to analyse microbial communities in broadleaved evergreen and deciduous forest soils of Shennongjia Mountain of Central China, a region known as ‘The Oriental Botanic Garden’ for its extraordinarily rich biodiversity. We observed higher plant diversity and relatively richer nutrients in the broadleaved evergreen forest than the deciduous forest. In odds to our expectation that plant communities shaped soil microbial communities, we found that soil organic matter quantity and quality, but not plant community parameters, were the best predictors of microbial communities. Actinobacteria , a copiotrophic phylum, was more abundant in the broadleaved evergreen forest, while Verrucomicrobia , an oligotrophic phylum, was more abundant in the broadleaved deciduous forest. The density of the correlation network of microbial OTU s was higher in the broadleaved deciduous forest but its modularity was smaller, reflecting lower resistance to environment changes. In addition, keystone OTU s of the broadleaved deciduous forest were mainly oligotrophic. Microbial functional genes associated with recalcitrant carbon degradation were also more abundant in the broadleaved deciduous forests, resulting in low accumulation of organic matters. Collectively, these findings revealed the important role of soil organic matter in shaping microbial taxonomic and functional traits.

Erratum to: Characterization of a genome-specific Gypsy-like retrotransposon sequence and development of a molecular marker specific for Dasypyrum villosum (L.) - Jie Zhang; Hai Long; Zhifen Pan; Junjun Liang; Shuiyang Yu; Guangbing Deng; Maoqun Yu (Journal of Genetics, 2013)

Characterization of a genome-specific Gypsy-like retrotransposon sequence and development of a molecular marker specific for Dasypyrum villosum (L.) - JIE ZHANG; HAI LONG; ZHIFEN PAN; JUNJUN LIANG; SHUIYANG YU; GUANGBING DENG; MAOQUN YU (Journal of Genetics, 2013)

Determination of GABAAα1 and GABAB1 receptor subunits expression in tissues of gilts during the late gestation - Zhiyong Fan; Yonghui Chen; Junjun Wang; Jinping Deng; Dexing Hou; Tiejun Li; Lingyuan Yang; Zhonghua Liu; Xiaosong Wu (Molecular Biology Reports, 2013)